Creating low skilled jobs by subsidizing market-contracted household work - Tilman Brück; John P. Haisken-DeNew; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2003)
We analyze the determinants of household work contracted in the German shadow economy. The German socio-economic household panel, which enumerates casual domestic employment, is used to estimate the demand for such household work. The regressors include regional wage rates, household income and several control variables for household composition. We find that the demand for household work in the shadow economy is very income elastic. This suggests that targeted wage subsidies, linked to household work agencies, would be very effective in raising the legal demand for domestic help. A wage subsidy of 50% of wage costs could thus establish up to 500,000 new jobs for previously unemployed or non-working low skilled workers. The net fiscal costs of such a scheme are about 6.200 Euro per full-time job. In addition, society benefits from more law enforcement and from a raised female labor supply, especially by highly qualified mothers.
Keywords: H24; D13; K42; J23; 330; labor demand; wage subsidy; household services; low skilled unemployment; shadow economy; GSOEP; Hauspersonal; Schwarzarbeit; Lohnsubvention; Ungelernte Arbeitskräfte; Arbeitsnachfrage; Wirtschaftspolitische Wirkungsanalyse; Deutschland